2011
DOI: 10.1177/0300985811417244
|View full text |Cite
|
Sign up to set email alerts
|

What Color Is the Skin of a Mouse?

Abstract: Laboratory mice naturally come in a large variety of colors ranging from black to white, brown to yellow, and spotted. 10,11 However, as obvious as this feature is, it refers to the color of the mouse's hair, not of its skin. Investigators are perpetually confused when they shave, clip, or chemically depilate mice to see black mice with pink skin or with patches of pink, grey, or black skin. Knowledge of basic physiological differences between mice and humans provides an obvious answer to this extremely common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Regulators of this process include developmentally important proteins such as members of the bone morphogenetic protein (BMP), hedgehog (HH) and wingless-related MMTV integration site (WNT) signalling pathways, as well as a variety of cytokines, transcription factors, and adhesion molecules (reviewed in [20] ). A simple way to examine the stage of hair follicle cycle at a gross level is to assess skin color in shaved animals; as follicles in anagen darken the skin due to melanocyte activity [21] . This process is non-invasive and requires minimal expertise, making it highly suitable for application to high throughput screens.…”
Section: Resultsmentioning
confidence: 99%
“…Regulators of this process include developmentally important proteins such as members of the bone morphogenetic protein (BMP), hedgehog (HH) and wingless-related MMTV integration site (WNT) signalling pathways, as well as a variety of cytokines, transcription factors, and adhesion molecules (reviewed in [20] ). A simple way to examine the stage of hair follicle cycle at a gross level is to assess skin color in shaved animals; as follicles in anagen darken the skin due to melanocyte activity [21] . This process is non-invasive and requires minimal expertise, making it highly suitable for application to high throughput screens.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, their sham treated mice (laser turned off) show normal mouse skin in telogen, the common, persistent stage found in adult mouse skin. The representative mouse treated with the laser on had normal hair follicles in late anagen (lacking clear evidence of inflammation in and around the follicles) ( Wikramanayake et al , 2012 ) which is found although infrequently in adult mice ( Sundberg and Silva, 2012 ). Alopecia in small foci in C3H/HeJ mice can be due to AA but also is not less commonly due to grooming behavior abnormalities (barbering, a form of trichotilomania).…”
mentioning
confidence: 99%
“…In contrast, rodents live an elusive lifestyle, so their pigments are mainly responsible for their hair colour and camouflage. This theory is supported by the fact that pigment in mice is produced in growing hair follicles and there is no to little pigmentation in interfollicular epidermis (19). Additionally, it has been described before that melanin, particularly pheomelanin, besides its protecting role could also serve as an effective photosensitize (41) and recent publication demonstrate its role in the formation of dark-CPDs (20).…”
Section: Discussionmentioning
confidence: 93%